PEMANFAATAN TEKNOLOGI SEDERHANA BERBASIS ARDUINO UNTUK PEMBERIAN MAKAN IKAN DENGAN KOMBINASI WAKTU DAN JUMLAH PAKAN - Muhammad Panca Prastyo; Irpan Kusyadi (CV. Multi Kreasi Media, 2023)
The problem that is commonly felt by fish farmers is how to increase business effectiveness efforts to find a tool for automatic fish feeding with the specified amount and time. One of them is how to do regular and scheduled fish feeding without using human labor to save cultivation costs. The current manual process is to sprinkle feed on the surface of the pond when it is time for the fish to eat. If the owner of the pond is unable to take care of the pond, the growth and health of the fish can be hampered. As a solution to these problems, a tool is needed that can automate the feeding of fish, which can run on a scheduled basis so that it can help facilitate fish farming without relying on human labor. The result of this research is the creation of an automatic fish feeder to help solve the problem of feeding in gouramy farming. So that cultivation becomes more efficient and fish farmers become more prosperous, and can help increase national food production.